The historical development of the concept of technology in Japan - Inutsuka, Yū (Mechane, 2020)
This paper draws upon the historical development of the concept of technology in Japan, dividing it into three periods: the period until the 18th century, wherein Chinese classics constituted the dominant influence; the 19th century, when concepts were reformed through translations of European languages; and the 20th century, when philosophers conducted theoretical debates, including the “Technology Controversy”. Japan has imported concepts related to technology from both China and the West, experiencing a mixture of the words, gi 技, gei芸, gijutsu 技術, geijutsu 芸術, art, technique, technology, and so forth. The development of philosophical analysis had to wait until the development of actual technologies and sciences in Japan itself. From the onset of the 20th century onward, philosophical debate became active among intellectuals such as Aikawa Haruki 相川春喜, who defined technology as a complex of material means of social labor, and Taketani Mitsuo 武谷三男, who stated that “technology is a conscious application of objective laws in human practice” and criticized Aikawa’s definition.